Precise Regulation of Interlayer Stacking Modes in Trinuclear Copper Organic Frameworks for Efficient Photocatalytic Reduction of Uranium(VI) - Zhi Gao; Sijia Lv; Yue Wang; Zhenzhen Xu; Yingtong Zong; Yuan Tao; Yingji Zhao; Xingyu Liu; Shuhui Yu; Mingbiao Luo; Nithima Khaorapapong; Ruikang Zhang; et al. (Advanced Science)
Abstract The interlayer stacking modes of 2D covalent‐organic frameworks (COFs) directly influence their structural features, ultimately determining their functional output. However, controllably modulating the interlayer stacking structure in traditional 2D metal‐free COFs, based on the same building blocks, remains challenging. Here, two trinuclear copper organic frameworks are synthesized successfully with different interlayer stacking structures: eclipsed AA stacking in Cu3‐PA‐COF‐AA and staggered ABC stacking in Cu3‐PA‐COF‐ABC, using the same monomers. Remarkably, various functionalities, including porosity and electronic and optical properties, can be effectively regulated by interlayer stacking. As a result, Cu3‐PA‐COF‐AA and Cu3‐PA‐COF‐ABC exhibit significantly different activities toward the photoreduction of U(VI), presenting a promising strategy for removing radioactive uranium pollution. Due to its broader visible‐light absorption range and superior photogenerated carrier migration and separation efficiency, Cu3‐PA‐COF‐AA achieves a U(VI) removal ratio of 93.6% without additional sacrificial agents in an air atmosphere—≈2.2 times higher than that of Cu3‐PA‐COF‐ABC (42.0%). To the best of the knowledge, this is the first study to elucidate the effect of interlayer stacking in COFs on the photocatalytic activity of U(VI) reduction. This finding may inspire further exploration of the structure‐function relationship in COFs as photocatalysts and their potential for photoinduced removal of radionuclides.